The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1088/0022-3727/44/9/095204
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the dependence of the temperature of high-intensity discharge (HID) lamp electrodes on the operating frequency by pyrometric measurements

Abstract: Abstract. Phase resolved temperature distributions are determined along a rod shaped tungsten electrode, by which an ac arc is operated within a model lamp filled with argon. Switched dc and sinusoidal currents are applied with amplitudes of several amps and operating frequencies being varied between 10 Hz and 10 kHz. The temperature is deduced from the grey body radiation of the electrode being recorded with a spectroscopic measuring system. Phase resolved values of the electrode tip temperature T tip and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 41 publications
1
20
0
1
Order By: Relevance
“…Reliable results were obtained with this method for electrodes operated with a dc-current [1,6,11]. But if the electrodes are operated with an ac-current the modulation of the electrode temperature is limited to a small area behind the electrode tip [15]. Therefore also the tip region with its exaggerated values of has to be taken into account when the integral of the heat balance is matched to the measured temperature distribution.…”
Section: Pyrometric Electrode Temperature Measurement (1λ-method)mentioning
confidence: 99%
See 3 more Smart Citations
“…Reliable results were obtained with this method for electrodes operated with a dc-current [1,6,11]. But if the electrodes are operated with an ac-current the modulation of the electrode temperature is limited to a small area behind the electrode tip [15]. Therefore also the tip region with its exaggerated values of has to be taken into account when the integral of the heat balance is matched to the measured temperature distribution.…”
Section: Pyrometric Electrode Temperature Measurement (1λ-method)mentioning
confidence: 99%
“…In this case it is easier to identify and remove locally excessive temperatures. A detailed discussion of the limited measuring accuracy of T tip is presented in [15,26]. It was shown that the phase resolved experimental determination of T tip is afflicted with an error of the order of ∆T tip ≈ 50 K.…”
Section: Pyrometric Electrode Temperature Measurement (1λ-method)mentioning
confidence: 99%
See 2 more Smart Citations
“…The behaviour of tungsten electrodes for HID lamps was investigated recently in the so called Bochum model lamp filled with argon [6] in dependence on the operating frequency being varied between 10 Hz and 10 kHz [28]. The Bochum model lamp is formed by a quartz tube, sealed vacuum-tight by two metallic end pieces with feedthroughs containing movable holders for the tungsten electrodes.…”
Section: Introductionmentioning
confidence: 99%